DAMPAK KRISIS EKONOMI TERHADAP KINERJA INDUSTRI KECILDI YOGYAKARTA = THE IMPACT OF ECONOMIC CRISIS ON THE PERFORMANCE OF SMALL SCALE TEMPE INDUSTRY IN YOGYAKARTA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
Economic crisis brought about the rising of imported input prices including price of soybean as a raw material for tempe processing. Tempe producers are small-scale units in the industry, they are price takers. After crisis, it is still profitable to produce and to market tempe although the BCR value (1.390) is smaller than the one before crisis (1.414). Factors that mostly affect the producers' benefits are price of tempe, price of soybean, and labor costs. The value of BEP after crisis is declining. It is easier to enter the industry because the need of capital is getting smaller. Combined with higher demand of tempe, the industry's viability is getting better. There are some 20 percent of new entrants in the industry.